IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL USING TRACKER VIDEO ANALYZER SOFTWARE TO IMPROVE STUDENTS’ SCIENTIFIC PROCESS SKILL IN PARABOLIC MOTION TOPIC - DWI KURNIAWAN, MAHENDRA (Inovasi Pendidikan Fisika, 2018)
This research is aimed to describe student?s scientific process skill after the student experienced a guided inquiry learning using Tracker video analyzer. The pre-experimental research adopted one group pre-test post-test design and applied to 76 number of student at 10th grade in SMA N 3 Surabaya. How the learning process was implemented, together with how the students conduct the experiment and their performance during experiment are all accessed by using evaluation sheets. Proceeding these evaluations, pre-test on the student?s scientific skill was completed. The results were subsequently compared with the post-test result that was running after the afore mentioned evaluations. The student?s response were also gathered to enrich the data. Subsequently the pre- and post- test data were analyzed using T-test and N- gain normalized test. It was obtained that the examined inquiry learning model in the topic of Parabolic Motion has increased the student?s scientific process skill significantly under the accusation coefficient (?) of 5%, while the n-gain was in a medium range. Keywords: Guided inquiry learning model, tracker video analyzer, student?s scientific process skill, Parabolic Motion